Five Decades of Tackling Models for Stiff Fluid Dynamics Problems A Scientific Autobiography - Zeytounian, Radyadour Kh.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Rationality - as opposed to 'ad-hoc' - and asymptotics - to emphasize the fact that perturbative methods are at the core of the theory - are the two main concepts associated with the Rational Asymptotic Modeling (RAM) approach in fluid dynamics when the goal is to specifically provide useful models accessible to numerical simulation via high-speed computing. This approach has contributed to a fresh understanding of Newtonian fluid flow problems and has opened up new avenues for tackling real fluid flow phenomena, which are known to lead to very difficult mathematical and numerical problems irrespective of turbulence. With the present scientific autobiography the author guides the reader through his somewhat non-traditional career; first discovering fluid mechanics, and then devoting more than fifty years to intense work in the field. Using both personal and general historical contexts, this account will be of benefit to anyone interested in the early and contemporary developments of an important branch of theoretical and computational fluid mechanics.
Introduction -- Ten Years in Armenia -- The Moscow Period With I.A. Kibel -- My French Scientific Career up to 2012 -- The Interrelationship Between NSF Equations and our RAM Approach -- Retrospective Summary -- Bibliography.
Keywords: Physics; Physical geography; Hydraulic engineering; Physics; Fluid- and Aerodynamics; Engineering Fluid Dynamics; Geophysics/Geodesy.; History and Philosophical Foundations of Physics; Numerical and Computational Physics